Anthelmintic Activity Of Water Extracts Of Trikatu Churna And Its Individual Ingredients On Indian Earthworms - P.R.MALVANKAR (International Journal of Pharma and Bio Sciences, 2012)
The Trikatu churna is one of the classical Ayurvedic preparations which is also called as “Three pungents”. It is prepared by mixing equal proportional mixture of powdered fruits of Piper nigrum L. i.e. maricha (Piperaceae), Piper longum L. i.e. pimpli (Piperaceae), & dried rhizomes of Zingiber officinale Roscoe i.e. ginger (Zingiberaceae).The present study was aimed to find out the anthelmintic activity of Trikatu churna & its individual ingredients on Pheritima postuma i.e. earthworms along with its preliminary phytochemical study. Powdered trikatu & its each component were extracted with water by the process of Maceration. The Albendazole suspension was used as standard. The time required for the paralysis & death was noted. It was found that all the samples possess good Anthelmintic activity at their highest concentrations.